Communication Pattern of Symbolic Interactionism Between Deaf Disabled Workers and Deaf Non-Disabled Workers at Ketje Jambi Coffee Cafe - Febiola Francisca; Damri Damri (Edumaspul: Jurnal Pendidikan, 2023)
This research was motivated by the discovery of deaf disability workers at the Ketje Jambi Coffee Cafe. The findings attracted researchers' curiosity about how communication patterns between workers. Based on these findings, a research problem formulation was obtained, namely "what is the pattern of symbolic interactionism communication between deaf disabled workers and deaf non-disabled workers?". So this study aims to find out what kind of communication pattern of symbolic interactionism that exists between workers with deaf disabilities and non-deaf workers during work activities at Ketje Jambi Coffee Cafe. This research uses qualitative research methods, where this research is to describe the situation empirically with a qualitative descriptive approach. Data collection techniques in this study were carried out by observation or observation, in-depth interviews and equipped with documentation. The data that has been analyzed from the results of this study will be described by researchers in narrative form. The results of the research conducted showed that the average interaction and communication carried out between deaf disabled workers and non-deaf disabled workers was carried out with symbolic interactionism communication patterns, interactions and communication between less active workers, communication that was established only limited to work, outside of their work busy with their respective worlds. It was concluded that communication between workers used the theory developed by George Herbert Mead. Keywords: Labor, Communication symbolic interactionism, deaf disabled worker.